Comparative in vitro biological activity analysis of Cuscuta reflexa Roxb. and C. campestris Yuncker. - Dar, Muhammad Ejaz ul Islam; Ashraf, Raheela; Shaheen, Hamayun; Firdous, Syeda Sadiqa; Mehmood, Ansar; Habib, Tariq; Hussain, Muhammad Altaf (Bangladesh Journal of Botany, 2020)
Cuscuta reflexa Roxb. and C. campestris Yuncker are widely used as medicinal plants in different areas of Azad Jammu and Kashmir. Keeping in view of their local uses, antibacterial, antioxidant and phytochemical investigations were carried out in the stem extracts. The antibacterial activities were carried out by Disc diffusion method against Gram positive (Staphylococcus aureus) and Gram negative (Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumonia) bacteria. Ampicillin was used as positive control. It was found that ethanol extract of both the plants were most active as compared to other extracts and S. aureus (Gram positive) was most sensitive bacterium compared to other tested Gram-negative bacteria. The antioxidant potential of the crude extracts of these plants was examined on the source of their scavenging activity of the stable 1, 1-diphenyl-2-picrrazyl hydrazyl (DPPH) free radical and found to possess good antioxidant. Preliminary phytochemical screening has shown the presence of several phytochemicals.